2008
DOI: 10.1073/pnas.0805662105
|View full text |Cite
|
Sign up to set email alerts
|

Specific mutations within the AT-rich region of a plasmid replication origin affect either origin opening or helicase loading

Abstract: Prokaryotic and eukaryotic replicons possess a distinctive region containing a higher than average number of adenine and thymine residues (the AT-rich region) where, during the process of replication initiation, the initial destabilization (opening) of the double helix takes place. In many prokaryotic origins, this region consists of repeated 13-mer motifs whose function has not yet been specified. Here we identify specific mutations within the 13-mer sequences of the broad-host-range plasmid RK2 that can resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…The iterons in plasmid origins are clustered similarly as the DnaA-boxes in chromosomal origins, on one side of an AT-rich DUE ( Fig. Both in vivo and in vitro tests revealed that specific alterations within the 13-mer sequences result in inhibition of the RK2 oriV opening and consequently in the lack of origin activity (Kowalczyk et al, 2005;Rajewska et al, 2008). The open complex formation at the plasmid origins is induced by Rep protein binding to the iterons; however, some plasmids still require DnaA to stabilize or enhance the origin unwinding (Kawasaki et al, 1996;Park et al, 1998;Kruger et al, 2001).…”
Section: Relevance Of Repeated Sequences Within At-rich Region For Dnmentioning
confidence: 99%
See 1 more Smart Citation
“…The iterons in plasmid origins are clustered similarly as the DnaA-boxes in chromosomal origins, on one side of an AT-rich DUE ( Fig. Both in vivo and in vitro tests revealed that specific alterations within the 13-mer sequences result in inhibition of the RK2 oriV opening and consequently in the lack of origin activity (Kowalczyk et al, 2005;Rajewska et al, 2008). The open complex formation at the plasmid origins is induced by Rep protein binding to the iterons; however, some plasmids still require DnaA to stabilize or enhance the origin unwinding (Kawasaki et al, 1996;Park et al, 1998;Kruger et al, 2001).…”
Section: Relevance Of Repeated Sequences Within At-rich Region For Dnmentioning
confidence: 99%
“…The DnaA and DnaC interactions with the ssDNA within the open AT-rich region are demonstrated for chromosomal origins (see paragraph above). Specific alterations within the 13-mer sequences, which do no affect origin opening, significantly disturb the E. coli DnaB helicase translocation from the DnaA-boxes to the RK2 AT-rich region (Rajewska et al, 2008). During the RK2 plasmid replication initiation, the E. coli DnaB helicase complex consisting of DnaA and DnaC proteins was shown at dsDNA DnaA-box repeats located outside the AT-rich region of the plasmid origin Pacek et al, 2001).…”
Section: Relevance Of Repeated Sequences Within At-rich Region For Dnmentioning
confidence: 99%
“…At the RK2 plasmid origin, the DnaBC-complex is bound to DnaAboxes by way of its interaction with DnaA (Pacek et al, 2001). TrfA then activates DnaB helicase and translocates it to the AT-rich region (Konieczny and Helinski, 1997;Rajewska et al, 2008). Different mechanisms have been observed for the DnaB recruitment process as utilization of specific replication proteins is host dependent.…”
Section: Replication Initiation At the Plasmid Origin: New Questionsmentioning
confidence: 97%
“…It is located 60 bp downstream of the iterons and contains four consensus 13-nucleotide repeat sequences: L, M1, M2, R. Three of them (L, M1, R) have the same orientation, while M2 has an opposite one. The position of these sequences is critical for origin opening and helicase loading during assembly of the replication complex (Doran et al, 1998;Konieczny et al, 1997;Kowalczyk et al, 2005;Rajewska et al, 2008Rajewska et al, , 2012.…”
Section: Plasmid Rk2 Origin Structurementioning
confidence: 98%
“…There is record of evidences state that specific mutations within the AT-rich region of replication origin affect either origin opening or helicase loading [5]. This is both in prokaryotic and eukaryotic replicons.…”
Section: Introductionmentioning
confidence: 99%